2007
DOI: 10.1111/j.1468-3083.2007.02511.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of desloratadine combined with dipyridamole in the treatment of chronic urticaria

Abstract: Chronic urticaria (CU) imposes profound impairment on patient's quality of life. Our study was done to evaluate the clinical efficacy and safety of desloratadine combined with dipyridamole, which is a platelet adhesion inhibitor in the treatment of CU. A randomized study was done in 64 autoimmunity CU patients with positive autologous plasma skin test (APST): 34 patients as treatment and 30 controls. The treatment group was treated with desloratadine and dipyridamole, and the control group was treated with des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Interestingly, D-dimer plasma levels dropped to normal values during CU remission (47). The activation of blood coagulation in patients with CU has been confirmed by other researchers (39,(48)(49)(50). In particular, Wang et al (39) found increased plasma levels of FVIIa (marker of the activation of the TF pathway), thrombin-antithrombin complex (marker of thrombin generation) and D-dimer (marker of fibrin degradation), which are correlated to each other in CU patients.…”
Section: Coagulation Biomarkers In Chronic Urticariasupporting
confidence: 67%
“…Interestingly, D-dimer plasma levels dropped to normal values during CU remission (47). The activation of blood coagulation in patients with CU has been confirmed by other researchers (39,(48)(49)(50). In particular, Wang et al (39) found increased plasma levels of FVIIa (marker of the activation of the TF pathway), thrombin-antithrombin complex (marker of thrombin generation) and D-dimer (marker of fibrin degradation), which are correlated to each other in CU patients.…”
Section: Coagulation Biomarkers In Chronic Urticariasupporting
confidence: 67%
“…Finally, in 2006 our group [29] demonstrates the activation of the coagulation cascade, supporting its involvement in chronic urticaria pathophysiology. Coagulation activation stemmed from eosinophil expression of tissue factor has been confirmed by us as well as by other groups [35][36][37][40][41][42] (marker of thrombin generation) and D-dimer (marker of fibrin degradation), which are correlated to each other in CU patients. Thrombin-antithrombin complex and D-dimer plasma levels are also found increased in CU by Fujii et al [40].…”
Section: Pathophysiological Aspectsmentioning
confidence: 58%
“…Furthermore, thrombin triggers mast cell degranulation [31] and may activate protease activated receptor-1 on mast cells [30] in animal models. The activation of blood coagulation in patients with CU has been recently confirmed by other independent researchers [39][40][41], and thus can be added to the mechanisms involved in CU (Fig. 3).…”
Section: Pathophysiological Aspectsmentioning
confidence: 74%
“…Interestingly, eosinophils might be in turn activated and recruited by mediators, cytokines, chemokines, or other as yet unknown factors released by mast cells [15][16][17][18]. The findings summarized above have been confirmed by several independent groups [19][20][21][22][23][24][25][26]. Thus, it seems likely that coagulation may play a role in the pathogenesis of chronic urticaria.…”
Section: Introductionsupporting
confidence: 59%